Vaccine efficacy against Covid-19 and its worrying variants - Paz, Candida Verônica de Andrade; Junior, Lauri Paulo Malacarne; Nascimento, Tássia Aimê; Camargo, Rafael Pereira; Ferreira, Marcelo Vicente Munin; Junior, Edilson Galeno de Sousa; Bastos, Carlos Eduardo Matos Carvalho; Pegoraro, Fábio; Gomes, Samara Tatielle Monteiro (Seven Editora, 2024)
Objective: To analyze the main COVID-19 vaccines available in Brazil and coverage against VOCs. Methods: 199 articles were found in PubMed, VHL and SciElo. The following were researched: Coronavirus, Vaccine, COVID-19, Evolution, Variant, Delta and Omicron. Works published in the period between 2019 and 2023. A total of 07 articles were selected. Results: The vaccine release sequence was Coronavac followed by Pfizer, Astrazeneca and Janssen with different mechanisms of action and dose schedules. Regarding VOCs, five were identified: Alpha, Beta, Delta, Gamma and Omicron. Conclusion: the pathogenicity of VOCs was increased and vaccine efficacy (IV) decreased. It is noteworthy that VE in the real scenario is affected by public health measures, individual behaviors, access to health services, and vaccine hesitancy, factors not considered in the studies. DOI:https://doi.org/10.56238/sevened2024.010-037